Answer:
(2.5, - 10 )
Step-by-step explanation:
given endpoints (x₁, y₁ ) and (x₂, y₂ ) then the midpoint is
(
,
)
here (x₁, y₁ ) = (- 16, - 12 ) and (x₂, y₂ ) = (21, - 8 ) , then
midpoint = (
,
) = (
,
) = (2.5, - 10 )
Answer:
23
Step-by-step explanation:
7 - 5p + 3q
p = 1, q = 7
Substitute in the values of "p" and "q", and solve;
7 - 5(1) + 3(7)
7 - 5 + 21
2 + 21
23
Answer:
1.
![(y - 5)(x + y)](https://tex.z-dn.net/?f=%28y%20-%205%29%28x%20%2B%20y%29)
2.
![{(x - y)}(x - y + a)](https://tex.z-dn.net/?f=%7B%28x%20-%20y%29%7D%28x%20-%20y%20%20%20%2B%20a%29)
3.
![(b - 3)(5b - 17)](https://tex.z-dn.net/?f=%20%28b%20-%203%29%285b%20-%2017%29)
Step-by-step explanation:
1. The given polynomial is
![x(y - 5) - y(5 - y)](https://tex.z-dn.net/?f=x%28y%20-%205%29%20-%20y%285%20-%20y%29)
We need to factor the second part to get:
![x(y - 5) + y(y - 5)](https://tex.z-dn.net/?f=x%28y%20-%205%29%20%20%2B%20%20y%28y%20-%205%29)
We factor y-5 to obtain:
![(y - 5)(x + y)](https://tex.z-dn.net/?f=%28y%20-%205%29%28x%20%2B%20y%29)
2. We have
![{(x - y)}^{2} - a(y - x)](https://tex.z-dn.net/?f=%20%7B%28x%20-%20y%29%7D%5E%7B2%7D%20%20-%20a%28y%20-%20x%29)
We again factor -1 from the second part to get:
![{(x - y)}^{2} + a(x- y)](https://tex.z-dn.net/?f=%20%7B%28x%20-%20y%29%7D%5E%7B2%7D%20%2B%20%20a%28x-%20y%29)
We now factor x-y to get:
![{(x - y)}^{2} + a(x- y)](https://tex.z-dn.net/?f=%20%7B%28x%20-%20y%29%7D%5E%7B2%7D%20%20%20%2B%20a%28x-%20y%29)
![{(x - y)}(x - y + a)](https://tex.z-dn.net/?f=%7B%28x%20-%20y%29%7D%28x%20-%20y%20%20%20%2B%20a%29)
3. We have
![2(3 - b) + 5 {(b - 3})^{2}](https://tex.z-dn.net/?f=%202%283%20-%20b%29%20%2B%205%20%7B%28b%20-%203%7D%29%5E%7B2%7D%20)
We factor negative 1 from the first part to get
![- 2(b - 3) + 5 {(b - 3})^{2}](https://tex.z-dn.net/?f=%20-%202%28b%20-%203%29%20%2B%205%20%7B%28b%20-%203%7D%29%5E%7B2%7D%20)
We now factor b-3 to get:
![(b - 3)( - 2 + 5(b - 3))](https://tex.z-dn.net/?f=%20%28b%20-%203%29%28%20-%202%20%2B%205%28b%20-%203%29%29)
We now simplify to get:
![(b - 3)( - 2 + 5b - 15) = (b - 3)(5b - 17)](https://tex.z-dn.net/?f=%20%28b%20-%203%29%28%20-%202%20%2B%205b%20-%2015%29%20%3D%20%28b%20-%203%29%285b%20-%2017%29)
Hello!
This is a rectangular prism
The equation to find the volume of a rectangular prism is
V = whl
v is volume
w is width
h is height
l is length
Put in the values you know
V = 12 * 4 * 2
Multiply
V = 96
The answer is 96 cubic feet
Hope this helps!